Effects of mouth breathing on facial skeletal development in children: a systematic review and meta-analysis - Ziyi Zhao; Leilei Zheng; Xiaoya Huang; Caiyu Li; Jing Liu; Yun Hu (BMC, 2021)
Abstract Background Mouth breathing is closely related to the facial skeletal development and malocclusion. The purpose of this systematic review and meta-analysis was to assess the effect of mouth breathing on facial skeletal development and malocclusion in children. Methods An electronic search in PubMed, the Cochrane Library, Medline, Web of Science, EMBASE and Sigle through February 23rd, 2020, was conducted. Inclusion criteria were children under 18 years of age with maxillofacial deformities due to mouth breathing. The risk of bias in nonrandomized studies of interventions (ROBINS-I) tool for controlled clinical trials. The Grading of Recommendation, Assessment, Development and Evaluation (GRADE) approach was used for the quality assessment. The included indicators were SNA, SNB, ANB, SN-OP, SN-PP, PP-MP, SNGoGn, MP-H, 1-NA, 1. NA, 1. NB, 1-NB, Overjet, Overbite, SPAS, PAS, and C3-H. Data concerning the mean difference in mesial molar movement and extent of canine retraction were extracted for statistical analysis. The mean differences and 95% confidence intervals were analyzed for continuous data. Review Manager 5.3, was used to synthesize various parameters associated with the impact of mouth breathing on facial skeletal development and malocclusion. Results Following full-text evaluations for eligibility, 10 studies were included in the final quantitative synthesis. In Sagittal direction, SNA (MD: − 1.63, P < 0.0001), SNB (MD: − 1.96, P < 0.0001) in mouth-breathing children was lower than that in nasal-breathing children. ANB (MD: 0.90, P < 0.0001), 1. NA (MD: 1.96, P = 0.009), 1-NA (MD: 0.66, P = 0.004), and 1-NB (MD: 1.03, P < 0.0001) showed higher values in children with mouth breathing. In vertical direction, SN-PP (MD: 0.68, P = 0.0050), SN-OP (MD: 3.05, P < 0.0001), PP-MP (MD: 4.92, P < 0.0001) and SNGoGn (MD: 4.10, P < 0.0001) were higher in mouth-breathing individuals. In airway, SPAS (MD: − 3.48, P = 0.0009), PAS (MD: − 2.11, P < 0.0001), and C3-H (MD: − 1.34, P < 0.0001) were lower in mouth breathing group. Conclusions The results showed that the mandible and maxilla rotated backward and downward, and the occlusal plane was steep. In addition, mouth breathing presented a tendency of labial inclination of the upper anterior teeth. Airway stenosis was common in mouth-breathing children. Trial registration crd-register@york.ac.uk, registration number CRD42019129198.